2009
DOI: 10.1002/sce.20311
|View full text |Cite
|
Sign up to set email alerts
|

Beginning teachers moving toward effective elementary science teaching

Abstract: ABSTRACT:We use a 10-year program of research centered on iterations of one elementary science methods course as a vehicle for exploring three important and interrelated goals for the learning of beginning elementary teachers. These include learning about inquiryoriented science teaching, using science curriculum materials effectively, and anticipating and working with students' ideas in instruction. For each goal we discuss how the literature informs our thinking, describe relevant aspects of our design of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 77 publications
4
67
0
3
Order By: Relevance
“…In this paper set, authors have identified other framework emphases, such as curriculum analysis (Davis & Smithey, 2009, this issue) and scientific modeling (Schwarz, 2009, this issue), both of which are important and productive areas to address through elementary science methods. My efforts to focus attention on scientific discourses and practices aimed at making meaning of science concepts have resulted in moving other learning foci to the background.…”
Section: Elementary Science Methodsmentioning
confidence: 99%
“…In this paper set, authors have identified other framework emphases, such as curriculum analysis (Davis & Smithey, 2009, this issue) and scientific modeling (Schwarz, 2009, this issue), both of which are important and productive areas to address through elementary science methods. My efforts to focus attention on scientific discourses and practices aimed at making meaning of science concepts have resulted in moving other learning foci to the background.…”
Section: Elementary Science Methodsmentioning
confidence: 99%
“…Novice science teachers tend to be unaware of students' ideas; when they do start to notice students' ideas, they tend to focus on more basic features like the concreteness or accuracy of these ideas (Schneider & Plasman, 2011). As science teachers gain experience, they are more likely to begin to consider how to build on students' prior ideas during instruction, how to link students' ideas to scientific ideas, and why students might find certain ideas conceptually difficult to learn-all significant content challenges that arise in the course of teaching in this area (Meyer, 2004;Schneider & Plasman, 2011).To develop students' ideas about key scientific concepts, research has also pointed to the importance of determining which instructional strategies and resources would be most beneficial for addressing specific student outcomes; this selection usually occurs through the critical analysis and use of curriculum materials (Davis, 2006;Davis & Smithey, 2009). In particular, research has suggested the importance of ensuring that science teachers can fluently discern which instructional resources to use to target specific learning goals, to provide insight into student thinking, and to address specific student challenges (Carlsen, 1991;Schneider & Plasman, 2011).…”
mentioning
confidence: 99%
“…En muchos casos los docentes proponen actividades experimentales demostrativas que no sirven como vehículos para aprender contenidos, tienen dificultades para poner sus ideas en práctica y en algunos casos hasta evitan enseñar ciencias (Davis y Smithey, 2009). Coincidimos con Moreno y Ferreyra (2004) en que comprender los fundamentos de la enseñanza por indagación y tener oportunidades durante la formación inicial para implicarse y reflexionar sobre este tipo de enseñanza son instancias que contribuyen a solucionar estos problemas.…”
Section: Diseño De Experimentosunclassified